MSCs-Derived Exosomes: Cell-Secreted Nanovesicles with Regenerative Potential - Marote, Ana; Teixeira, Fábio G.; Mendes-Pinheiro, Bárbara; Salgado, António J. (Frontiers in Pharmacology, 2016)
Exosomes are membrane-enclosed nanovesicles (30-150 nm) that shuttle active cargoes between different cells. These tiny extracellular vesicles have been recently isolated from mesenchymal stem cells (MSCs) conditioned medium, a population of multipotent cells identified in several adult tissues. MSCs paracrine activity has been already shown to be the key mediator of their elicited regenerative effects. On the other hand, the individual contribution of MSCs-derived exosomes for these effects is only now being unraveled. The administration of MSCs-derived exosomes has been demonstrated to restore tissue function in multiple diseases/injury models and to induce beneficial in vitro effects, mainly mediated by exosomal-enclosed miRNAs. Additionally, the source and the culture conditions of MSCs have been shown to influence the regenerative responses induced by exosomes. Therefore, these studies reveal that MSCs-derived exosomes hold a great potential for cell-free therapies that are safer and easier to manipulate than cell-based products. Nevertheless, this is an emerging research field and hence, further studies are required to understand the full dimension of this complex intercellular communication system and how it can be optimized to take full advantage of its therapeutic effects. In this mini-review, we summarize the most significant new advances in the regenerative properties of MSCs-derived exosomes and discuss the molecular mechanisms underlying these effects.